Reading and writing direction effects on the aesthetic appreciation of photographs. Issue 3 (4th May 2017) - Chahboun, Sobh; Flumini, Andrea; Pérez González, Carmen; McManus, I. Chris; Santiago, Julio
ABSTRACT: Does reading and writing direction (RWD) influence the aesthetic appreciation of photography? Pérez González showed that nineteenth-century Iranian and Spanish professional photographers manifest lateral biases linked to RWD in their compositions. The present study aimed to test whether a population sample showed similar biases. Photographs with left-to-right (L–R) and right-to-left (R–L) directionality were selected from Pérez González's collections and presented in both original and mirror-reversed forms to Spanish (L–R readers) and Moroccan (R–L readers) participants. In Experiment 1, participants rated each picture for its aesthetic pleasingness. The results showed neither effects of lateral organization nor interactions with RWD. In Experiment 2, each picture and its mirror version were presented together and participants chose the one they liked better. Spaniards preferred rightward versions and Moroccans preferred leftward versions. RWD therefore affects aesthetic impressions of photography in our participants when people pay attention to the lateral spatial dimension of pictures. The observed directional aesthetic preferences were not sensitive to the sex of the model in the photographs, failing to support expectations from the hypotheses of emotionality and agency. Preferences were attributable to the interaction between general scanning strategies and scanning habits linked to RWD.